A estrutura da obra Scito te Ipsum de Pedro Abelardo (Razão e Fé, 2026)
The objective of this work is to present the structure of the work Scito te Ipsum by Peter Abelard. This philosopher had a great influence in the 12th century, especially in the field of education. The work Scito te Ipsum is divided into two books: the first deals with vices and sin, while the second addresses virtues. This ethical work consists of 26 chapters subdivided into sections. Abelard wrote it with the intention of deepening the discussion on morality from a Christian perspective. However, he faced strong opposition from Saint Bernard of Clairvaux, who instigated the condemnation of his alleged heresies by theChurch. In general, considering Abelard’s academic trajectory, the role of ratio (Logic, Dialectic) in Scito te Ipsum, and the fundamental principles of his work, this study seeks to explore solutions to the problem of sin.